Synthesis and characterization of type B gelatin and silica nanoparticles with a novel rational designed translocating and antifungal peptide (2022)
Gelatin and silica nanoparticles have been developed as nanocarriers of drug delivery systems because of their high biocompatibility. This study aims to synthesize type B gelatin (GNPs) and silica nanoparticles (SNPs) with a novel rational designed peptide to be use as translocating and antifungal agent. Also, the physical, chemical and biocompatibility properties of the obtained nanoparticles were compared. Gelatin nanoparticles were synthesized by the double desolvation method and the silica nanoparticles by the hydrolysis and polycondensation of TEOS in a mixture of ammonia, alcohol, and water. The obtained nanobioconjugates were characterized by thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). FTIR results show that the peptide was immobilized correctly in both nanoparticles. Furthermore, the NPs were tested for their ability to induce hemolysis and platelet aggregation. The obtained NPs with the KS-peptide show a low hemolytic percentage (less than 5%) and a lower tendency to induce platelet aggregation. Finally, they were tested upon an antifungal assay with C. tropicalis, C. krusei, C. albicans and Cryptococcus neoformans; the NPs show a tendency to not inhibit the growth of fungi.